Strategies to improve detection and management of human parechovirus infection in young infants. Issue 2 (February 2019) - Kadambari, Seilesh; Harvala, Heli; Simmonds, Peter; Pollard, Andrew J; Sadarangani, Manish
Summary: Human parechovirus infections are the second most common cause of viral meningitis in children. These infections are most frequently seen in infants younger than 90 days. Clinical manifestations include encephalitis, meningitis, myocarditis, and sepsis, which can lead to serious neurodevelopmental sequelae in young infants. Molecular techniques, including PCR assays, are the preferred diagnostic methods and have contributed to an increase in reported cases, along with an increasing awareness of the causal role of human parechovirus in infant diseases. However, focused clinical and diagnostic investigations of human parechovirus in infants and the use of their results in management is varied, partly because of the scarcity of robust incidence data and spectrum of clinical presentations of the infection. In this Review, we outline clinical cohort and epidemiological studies that can be used to inform the evidence-based management of young infants with human parechovirus disease and identify key research priorities. An improved understanding of the pathogenesis and epidemiology of these infections is required to inform an evidence-based approach to diagnosis and treatment in the future.